Smart organic bin / Nurfarah Hidayu Abdul Rahman, Nurul Ain Athirah Muhamad and Haslinda Rahim - Abdul Rahman, Nurfarah Hidayu; Muhamad, Nurul Ain Athirah; Rahim, Haslinda (2018)
The team is developing a Smart Organic Bin, that has been improved and revised to replace the existing product. The product is invented to recycle the food waste into ready-to-use fertilizer that can be used for gardening or landscaping. It is to overcome the problem of excessive food waste in household. It is a new product to replace existing product with a functional enhancement which is additional to the automatic odor control feature.